Literary discourse and film discourse in terms of art discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Most often the discourse-analysis theories focus on the following discourse-objects: discourses of everyday communication, institutional discourses, public discours, political discourse, media discourses, art discourses etc. So the article is about the art discourse which is one of the main kinds of discourse. The art discourse has not received wide extention in modern linguistics yet and seems to be understudied. There are the literary discourse, the music discourse, the visual art discourse, the model discourse, etc. in the sphere of art. The art discourse reflects modern phenomena with the help of language means. It represents both a textual unity, which interprets an art object together with extra textual factors, and the communication activity where should present a sender and a recipient of information. Due to the above-mentioned, not just the literary discourse but also the film discourse are passed in review in this article. In that article we consider literary discourse as a communicative process of information delivery from an author to a reader. As a result, a kind of a message appears. The article also deals with features and functions of the literary discourse and the film discourse. Main features of the literary discourse are a written form, wholeness and completeness, polymorthy, blured distinction between the truth and a lie towards an objective reality. Functions of the literary discourse are the following: informative, creative. The film discourse is considered both in narrow and broad senses in the article. In a narrow sense, the film discourse is “an oral, written, visual message, expressed with verbal / visual signs”. In broader sense, the film discourse is a process of creating, playing out and percepting the film. This process includes the synthesis of the participants of the discourse, i.e. their speech, time and space of their co-operation. Action, formation of characters and their relationship, and also the development of their natures happen with the help of this synthesis. Main features of the film discourse are wholeness and completeness, usage of the film language tools, the synthesis of a personality's speech activity and a non-verbal component, presence of broad extratextual factors. Main functions of the film discourse are informative and the function of influence. Therefore, according to criteria of genre and functional style, the literary discourse and the film discourse refer to the art discourse. The most important object of studying both kinds of art discourse is works of art, i.e. fiction and feature films accordingly.
Keywords: literary discourse; film discourse; art discourse; discourse analysis